Association between red blood cell distribution width to albumin ratio and prognosis of patients with sepsis: A retrospective cohort study - Xu, Weigan; Huo, Jianyang; Chen, Guojun; Yang, Kangyi; Huang, Zuhua; Peng, Lina; Xu, Jingtao; Jiang, Jun (Frontiers in Nutrition, 2022)
Background: Red blood cell distribution width (RDW) to albumin ratio (RAR) is associated with poor prognosis in diabetic comorbidities and cancer. However, the association between RAR and prognosis in patients with sepsis remains unclear, which was investigated in this study. Methods: We conducted a retrospective cohort study based on the Medical Information Mart for Intensive Care (MIMIC) IV version 2.0 database. The primary outcome of this study was 28-day mortality. Secondary outcomes included 90-day mortality, in-hospital mortality, length of hospital stay, and length of intensive care unit (ICU) stay. Multivariate regression analysis and subgroup analysis were performed to investigate the association between RAR and prognosis in patients with sepsis. Results: A total of 14,639 participants were included in this study. The mean age of the participants was 65.2±16.3 years and the mean RAR was 5.5±1.9 % /g/dl. For 28-day mortality, after adjusting for covariates, HRs [95% confidence intervals (CIs)] for tertiles 2 (4.4 - 5.8) and 3 (RAR > 5.8) were 1.33 (1.20, 1.46) and 1.98 (1.79, 2.19), respectively. Similar results were observed for 90-day mortality and in-hospital mortality. According to Kaplan-Meier curve analysis, the higher RAR group had higher 28-day mortality and 90-day mortality. Receiver operating characteristic (ROC) curve analysis demonstrated that RAR predicted 28-day mortality better than RDW or albumin alone. Conclusion: Our study shows that RAR is significantly associated with poor clinical prognosis in sepsis. RAR has good predictive power for 28-day mortality in patients with sepsis and is superior to RDW or albumin alone.